Jumlah Profil Pasien dengan Gaster Perforasi di RSUD Tabanan Tahun 2021-2022: - - I Putu Gosen Partama; Made Kurniawan; I Gusti Ngurah Sumantri; Anak Agung Gede Indraningrat (Warmadewa University, 2025)
Gastric perforation is a life-threatening surgical emergency that frequently arises as a complication of peptic ulcer disease and carries a high mortality rate. This study aimed to describe the clinical profile and outcomes of gastric perforation patients treated at Tabanan Hospital. A retrospective review of medical records was conducted for all gastric perforation cases from January 2021 to December 2022. Seventeen patients were identified. Most were older than 50 years (94%) and female (65%). More than half had no formal education and were unemployed. A history of nonsteroidal anti-inflammatory drug use was present in 59% of cases. Most patients arrived more than 6 hours after symptom onset, and many presented in critical condition, including shock (24%), tachypnea (76%), and acute kidney injury (53%). Intraoperatively, most perforations were located in the gastric antrum (65%) and measured 1–2 cm (82%). Postoperatively, hypoalbuminemia (94%), sepsis (35%), and pneumonia (24%) were common. The in-hospital mortality rate was 29%. In conclusion, gastric perforation at our institution predominantly affected elderly patients, with delayed presentation, severe initial clinical status, and high complication and mortality rates. Enhanced community awareness of ulcer symptoms, early referral, rational NSAID use, and timely surgical intervention are essential to improving outcomes.